2009
DOI: 10.1021/jf902117v
|View full text |Cite
|
Sign up to set email alerts
|

Isotope Labeling Studies on the Origin of 3,4-Hexanedione and 1,2-Butanedione in an Alanine/Glucose Model System

Abstract: Although the importance of alpha-dicarbonyl compounds as reactive intermediates in the Maillard reaction and as precursors of heterocyclic and odor-active compounds is well-established, however, the detailed origin of many alpha-dicarbonyl compounds such as 3,4-hexanedione and 1,2-butanedione still remains unknown. Using glucose and glyoxal with labeled [(13)C-1]alanine, [(13)C-2]alanine, [(13)C-3]alanine, and [(15)N]alanine, the mechanism of their formation was investigated using the label incorporation patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Formaldehyde and acetaldehyde formed from Gly and Ala also participate in the chain elongation process of sugar-derived α-dicarbonyl compounds and these α-dicarbonyl compounds with ethyl and/or methyl substituents from amino acids may be involved in alkylpyrazine formation through oxidative or non-oxidative pathways. In the oxidative pathway, the dihydroalkylpyrazine intermediates readily oxidise to form the corresponding alkylpyrazines and this has been shown to be a major pathway (Chu & Yaylayan, 2009). Formaldehyde and acetaldehyde formed from Gly and Ala participate in the non-oxidative pathway of pyrazine formation and yield ethyl or methyl substituted alkylpyrazines upon dehydration of the alkylated site of dihydropyrazines.…”
Section: Effect Of Amino Acid Addition On Alkylpyrazine Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…Formaldehyde and acetaldehyde formed from Gly and Ala also participate in the chain elongation process of sugar-derived α-dicarbonyl compounds and these α-dicarbonyl compounds with ethyl and/or methyl substituents from amino acids may be involved in alkylpyrazine formation through oxidative or non-oxidative pathways. In the oxidative pathway, the dihydroalkylpyrazine intermediates readily oxidise to form the corresponding alkylpyrazines and this has been shown to be a major pathway (Chu & Yaylayan, 2009). Formaldehyde and acetaldehyde formed from Gly and Ala participate in the non-oxidative pathway of pyrazine formation and yield ethyl or methyl substituted alkylpyrazines upon dehydration of the alkylated site of dihydropyrazines.…”
Section: Effect Of Amino Acid Addition On Alkylpyrazine Formationmentioning
confidence: 99%
“…Condensation of two α-amino carbonyl compounds produces a dihydropyrazine and subsequent oxidation yields a pyrazine (Shibamoto & Bernhard, 1977). Methyl substitution in pyrazines may originate from methylglyoxal (via 2-aminopropanal or 1-amino-2-propanone), 1-hydroxy-2-propanone (via 2-aminopropanal), 2,3-butanedione and 3hydroxy-2-butanone (via 3-amino-2-butanone) followed by oxidation of the corresponding dihydropyrazines (Chu & Yaylayan, 2009). Ethyl substitution may come from 2-oxobutanal, 2,3pentanedione and 3,4-hexanedione via this oxidative pathway (Chu & Yaylayan, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the above model system studied, the only expected pyrazine is the completely unlabeled tetramethylpyrazine because the only α-dicarbonyl present in the model system was unlabeled 2,3-butanedione. As mentioned above, not only were other pyrazines detected but they also exhibited various percentages of 13 C-2 atom incorporation patterns, as presented in Table 1. The formation of completely unlabeled pyrazines can only be explained by the degradation of 2,3-butanedione into glyoxal and pyruvaldehyde, the two unlabeled α-dicarbonyls needed for their formation (see Figure 2).…”
Section: ■ Results and Discussionmentioning
confidence: 74%
“…10 As was mentioned above, this pyrazine was formed in the 2,3butanedione/glycine model system with the contribution of C-2 atoms from glycine, where-isotope labeling studies have indicated the incorporation of one (20%) and two (50%) such carbon atoms from 13 C-2 glycine; similarly, 53% of trimethylpyrazine was also found to be formed from the contribution of multiple C-2 atoms from glycine (Table 2). The Strecker mechanism cannot justify the incorporation of 13 C-2 atoms into the ring system of the pyrazines. There is evidence from the mass spectral data of 2,3-dimethylpyrazine and 2,3,5trimethylpyrazine that the label incorporation occurred at the ring carbon atoms of the pyrazines (see Figure 3).…”
Section: ■ Results and Discussionmentioning
confidence: 99%